Cultura acadêmica e tecnologias intelectuais digitais: ensinar e aprender com blogs educativos no ensino superior - Bezerra, Lebiam Tamar Silva (2011)
Culture as the main organizer of ways of being and living of people has become fundamental, especially after the second half of the twentieth century and the twenty-first century. Since 1960, studies conducted by Cultural Studies, especially by Media Studies, have initiated the problematization of the relationship between culture and media in the constitution of social relations. The epistemological challenge of this research consists of analyzing the hybridization of the academic culture with a cyberculture from mediations between learners and digital intellectual technologies in educational blogs in higher education. Therefore, proposes a critical reflection on the meanings produced for teaching and learning practices in the use of academic education blogs, mapping the views of academic culture and outlining a provisional and transitory map of its hybridization with a cyberculture, based on the methodological assumptions of virtual ethnography. Originated from the theoretical intercultural perspective proposed by Canclini and Martín-Barbero, this study interconnects concepts of learning, learners, digital intellectual technology, academic culture, cyberculture and hybridization, emphasizing the political aspects involved in interculturality and the relevance taken on pragmatic aspects that, in general, have predominated in the conceptions and practices of cultural appropriation and the use of technologies in educational institutions. The blogosphere is the empirical field chosen for this virtual ethnography. Five teachers of federal institutions of higher education in Brazil participated in this research. Data were collected through semi-structured interviews and documentary analysis of the interface and records contained in the posts and comments from five educational blogs that comprised the study sample. The data were treated following the analytical approach to the ethnographic record, proposed by Atkinson, which generates a series of thematic headings and coding schemes to outline a conceptual network for the organization and presentation of the results. The analysis allows concluding that the mediations between learners and digital intellectual technologies can promote and / or restrict the hybridization of the academic culture with the a cyberculture. Accordingly, it was possible to confirm the thesis that teaching and learning are continually (re) defined in the practical use of academic educational blogs, in both situations. These redefinitions refer, above all, to the redistribution of power in the relationship between learners and teachers and to the discussion of the episteme of teaching at university. As verified, cultural hybridization hold a virtuality to transform academic practices. However, the resulting hybrid practices are always consolidated by continuities and ruptures, coming from the practices of the academic culture and practices of the cyberculture that hybridized.